2012
DOI: 10.1099/ijs.0.031344-0
|View full text |Cite
|
Sign up to set email alerts
|

Massilia flava sp. nov., isolated from soil

Abstract: A Gram-stain-negative, rod-shaped bacterium, designated strain Y9 T , was isolated from a soil sample collected in Ningxia Province in China and was characterized to determine its taxonomic position. Strain Y9 T contained Q-8 as the predominant ubiquinone. Major fatty acid components were summed feature 3 (C 16 : 1 v7c and/or iso-C 15 : 0 2-OH) and C 16 : 0 . The major polar lipids were phosphatidylethanolamine, phosphatidylglycerol and diphosphatidylglycerol. The G+C content of the genomic DNA of strain Y9 T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 28 publications
5
24
0
Order By: Relevance
“…This is consistent with the capacity for coumaric acid utilization by several members of this genus, such as A. hydrophila, A. sobria, and A. caviae [75]. Furthermore, Sphingobium paulinellae, algicola, and scionense [76,77] utilize Nacetylglucosamine and Massilia flava has tryptophane deaminase activity [78]. The congruence with known physiological traits of described genera indicates that our combined approach can also provide information on the substrate adaptations of not-yet-cultured rhizosphere bacteria.…”
Section: Specific Responses Of Bacterial Otus To Defined Root Exudatessupporting
confidence: 77%
“…This is consistent with the capacity for coumaric acid utilization by several members of this genus, such as A. hydrophila, A. sobria, and A. caviae [75]. Furthermore, Sphingobium paulinellae, algicola, and scionense [76,77] utilize Nacetylglucosamine and Massilia flava has tryptophane deaminase activity [78]. The congruence with known physiological traits of described genera indicates that our combined approach can also provide information on the substrate adaptations of not-yet-cultured rhizosphere bacteria.…”
Section: Specific Responses Of Bacterial Otus To Defined Root Exudatessupporting
confidence: 77%
“…The relative values for bacterial genera are indicated by color intensity with the legend indicated at the top right corner been reported to utilize testosterone under both oxic and anoxic conditions. The genus Massilia was mainly isolated from the blood of an immunocompromised patient (Lindquist et al 2003) and has been recently found in environmental samples, such as soil samples from China and in the drinking water distribution system in Seville (Spain) (Gallego et al 2006;Wang et al 2012a). In this study area, Steroidobacter was found to closely relate to Cd content (R 2 =0.729, P<0.05), while Massilia had significant correlation with Cd and Cr contents (R 2 =0.718, P<0.05; R 2 =0.671, P<0.05).…”
Section: Bacteria With Potential Resistance To Heavy Metalsmentioning
confidence: 99%
“…The genus Massilia La Scola et al 2000 belongs to the betaproteobacterial family Oxalobacteraceae , together with the closely related genera Telluria , Pseudoduganella , Duganella and Janthinobacterium (Kämpfer et al , 2011; Wang et al , 2012; Kong et al , 2013). The genus was described on the basis of a single clinical isolate from the blood of a 25-year-old immunocompromised patient with meningoencephalitis, which was assigned to the type species Massilia timonae (La Scola et al , 1998).…”
mentioning
confidence: 99%